Early crediting of emissions reduction: A panacea or Pandora's Box? - Axel Michaelowa; Marcus Stronzik (Fondazione Eni Enrico Mattei (FEEM), 1999)
The Kyoto Protocol sets legally binding emission targets for industrialised countries without accounting for reductions carried out prior to 2008, the beginning of the first commitment period. There exists only one exception, the project-based Clean Development Mechanism where credits accrue from 2000. Two other possible ways to allow crediting for early reductions are discussed in this paper, a domestic scheme and early Joint Implementation. Part of the emission budget is allocated to entities that prove pre-2008 emission reduction. The implications of these concepts are analysed on a macro as well as on a micro level taking the domestic and international commitments into account. They can lead to a strong redistribution and are prone to free riding. Credited reductions strongly depend on the choice of baseline-setting methodology. Moreover, compliance can be endangered as sectors that are less competitive and do not participate may be confronted with higher reduction commitments from 2008. We conclude that early crediting makes sense if it is built on conservative baselines, sets incentives for innovation and provides for institutional learning. The current bill discussed in the U.S. does not meet these criteria.
Keywords: D61; K32; K33; Q25; Q28; 330; Early crediting; Emissions trading; Joint implementation; Clean development mechanism; Climate change policy; Kyoto Protocol; Klimaschutz; Umweltpolitik; Luftreinhaltung; Selbstverpflichtung; Trittbrettfahrerverhalten; Theorie